Preoperative predictors of difficult oropharyngeal exposure for transoral robotic surgery: The Pharyngoscore. Issue 10 (16th June 2021) - Gaino, Francesca; Gorphe, Philippe; Vander Poorten, Vincent; Holsinger, F. Christopher; Lira, Renan B.; Duvvuri, Umamaheswar; Garrel, Renaud; Van Der Vorst, Sebastien; Cristalli, Giovanni; Ferreli, Fabio; De Virgilio, Armando; Giannitto, Caterina; et al.
Abstract: Background: Insufficient exposure may require termination of procedure in transoral robotic surgery (TORS). The aim of study was to develop a "Pharyngoscore" to quantify the risk of difficult oropharyngeal exposure (DOE) before TORS. Methods: Three‐hundred six patients undergoing any surgical procedure at one Academic Hospital were prospectively enrolled. Oropharynx was exposed with Feyh–Kastenbauer retractor. Exposure was evaluated by direct and endoscopic visualization of the four oropharyngeal subsites. Preoperative clinical/anthropometric parameters were studied in good oropharyngeal exposure and DOE groups. Logistic regression was performed to explore association between clinical/anthropometric parameters and DOE. Statistically significant parameters at multivariate analysis were incorporated into a nomogram. Results: Sixty‐five (21.2%) subjects were characterized by DOE. Variables associated with DOE at univariate analysis were male ( p = 0.031), modified Mallampati Class (MMC) ≥ III ( p < 0.001), smaller interincisor gap ( p < 0.001), and larger neck circumference ( p = 0.006). MMC, interincisor gap, and neck circumference were significant at multivariate analysis and were presented with a nomogram for creating the Pharyngoscore. Conclusions: The Pharyngoscore is a promising tool for calculating DOE probability before TORS.